Kompetensi Inovatif Guru Sekolah Dasar - Iis Hasanah; Siti Nursholihah; Laesti Nurishlah; Ani Sri Mulyani (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This research discusses teacher readiness in integrating innovative competencies in teaching and the role of openness to experience in this process. Teachers' innovative competence is crucial in improving the quality of education, while openness to experience plays an important role in facilitating creativity, willingness to experiment, awareness of change, and collaboration in a professional environment. Developing teachers' innovative competence does not only require an understanding of innovative learning techniques, but also requires the development of an adequate attitude of openness to experience. Proper support in increasing the level of openness to teachers' experiences can be key to improving the quality of teaching and learning in schools.